DIAGNOSIS OF PARASITIC DISEASES IN BIVALVE MOLLUSCS - R.CAROLINE JEBA,; S.ANITHA, (International Journal of Pharma and Bio Sciences, 2015)
The class bivalves belongs to the phylum mollusc. The Class Bivalves with about 7500 species, includes animals with two shell valves such as mussels, oysters, scallops clams etc. Mollusc resources are very much useful to coastal communities and others in the different ways and forms. Efforts have to be made to conserve and protect this resources for the sustainable development of coastal ecosystem and the dependent population. Many molluscs are a great source of food for man in many parts of world. Molluscs are eaten by humans. Many bivalve molluscs are dangerous to humans to avoid this project has been done by identifying the major parasites affecting the bivalve molluscs which also helps to develop the mollusc population by treating the infected molluscs. This was screened by conventional microscopic method, histopathological technique and by molecular method (PCR).